Exercise-induced haemoptysis as a rare presentation of a rare lung disease. Issue 9 (7th June 2016) - Mihalek, Andrew D; Haney, Carissa; Merino, Maria; Roy-Chowdhuri, Sinchita; Moss, Joel; Olivier, Kenneth N
Abstract : Amyloid primarily affecting the lungs is a seldom seen clinical entity. This case discusses the work-up of a patient presenting with exercise-induced haemoptysis and diffuse cystic lung disease on radiographic imaging. The common clinical and radiographic findings of diffuse cystic lung diseases as well as a brief overview of pulmonary amyloid are presented.